Gasification of waste materials : technologies for generating energy, gas and chemicals from MSW, biomass, non-recycled plastics, sludges and wet solid wastes /: technologies for generating energy, gas and chemicals from MSW, biomass, non-recycled plastics, sludges and wet solid wastes. (2017) - Ciuta, Simona; Tsiamis, Demetra; Castaldi, Marco J, 1970-
No abstract available